Perancangan Dan Implementasi Aplikasi Pemesanan Online Berbasis Web Pada Kedai Barokah Cilamaya - Alvian Septiana; Aji Primajaya; Iqbal Maulana (Jurnal Ilmiah Wahana Pendidikan, 2022)
A shop is a temporary structure used to prepare and sell food and drink to the public, usually where large groups of people are in the wild. The Barokah shop in the Cilamaya area is a food and beverage shop with an easy-to-find location and relatively cheap menu prices. However, the food menu ordering system at Kedai Barokah still uses the usual method. To order food, the customer must come to the shop and the waiter delivers a menu list and the waiter records the customer's order manually. From the description above, the author wants to do research on Kedai Barokah Cilamaya which still uses the manual method in placing orders. In this study the author will create a web-based system using the waterfall method to handle the problem of ordering food and drinks that are still offline. It is hoped that the customer or customer will feel helped and facilitated in using the online ordering service.scanning method is conducted. Testing is done by means of vulnerability assessments using the acunetix application to analyze security on a BEM Fasilkom Unsika website.